Investigation of the effects of intravenous magnesium sulphate on cardiac rhythm in acute myocardial infarction. Issue 2 (February 1994) - Roffe, C.; Fletcher, S.; Woods, K. L.
Abstract : OBJECTIVE--To examine the effect of doubling serum magnesium concentration on the incidence of arrhythmias in patients with suspected acute myocardial infarction. DESIGN--Randomised double blind clinical trial. SETTING--Coronary care unit of a teaching hospital. PATIENTS--Clinical data were collected on 2316 randomised patients with suspected acute myocardial infarction. Holter monitoring was performed in a subgroup of 70 patients and analysed in 48 patients in whom acute myocardial infarction was confirmed. INTERVENTIONS--By random allocation, patients received either an intravenous loading dose of 8 mmol magnesium sulphate over five minutes plus 65 mmol over the next 24 hours, or equal volumes of saline. MAIN OUTCOME MEASURES--(a) Clinically documented arrhythmias; (b) use of antiarrhythmic treatments, cardioversion, and insertion of a pacemaker; (c) incidence of all abnormal rhythms during Holter monitoring. RESULTS--In the main trial the incidence of rhythm disturbance while in the coronary care unit (expressed as the odds ratio (OR) for magnesium: placebo and its 95% confidence interval) was not significantly different between treatment groups for ventricular fibrillation (OR 0.74; 0.46 to 1.20), ventricular tachycardia (OR 0.87; 0.63 to 1.20), supraventricular tachycardia (OR 0.69; 0.38 to 1.26), atrial fibrillation (OR 0.92; 0.69 to 1.23), or heart block of any degree (OR 1.17; 0.83 to 1.65). Sinus bradycardia was significantly more common in the magnesium group (OR 1.38; 1.03 to 1.85; p = 0.02). These findings were corroborated by the use of treatments for rhythm disturbance and the data from Holter monitoring. CONCLUSION--The regimen of intravenous magnesium sulphate used here had no significant effect on arrhythmia in acute myocardial infarction. The reduction in mortality that has been shown with this form of treatment is not attributable to suppression of life threatening rhythm disturbances.